Stress and coping among the socially-involved religious of the Daughters of Mary of the Assumption - Gimeno, Milagros L. (Animo Repository, 1989)
This study attempted to find out the sources and level of stress and personality traits among the socially-involved religious of the Congregation of the Daughters of Mary of the Assumption in Davao, Philippines. Furthermore, the study identified the coping mechanisms utilized by the Sisters in dealing with stressful life situations. It also measured the effectiveness of coping strategies employed by the Sisters when confronted with stressful events. Thus, this study sought to answer the following questions: 1. What are the sources and level of stress of the Sisters? 2. What are their personality traits, as measured by the Comrey Personality Scale? 3. Is there a significant relationship between the over-all, by area and by item level of stress of the Sisters and the following personality traits? 1. Trust b. Orderliness c. Social Conformity d. Activity e. Emotional stability f. Extraversion g. Masculinity h. Empathy 4. What coping strategies do the Sisters used and how effective do they perceive them to be? The researcher employed the descriptive research method to identify the sources and levels of stress among the Sisters and to determine the relationship between stress level and personality traits. It also described the coping mechanisms that the Sisters used as they experienced stress in life and determined how effective these coping strategies were. The subjects of the study were twenty-nine out of fifty sisters of the Daughters of Mary of the Assumption in the Philippines from the novices to the perpetually professed Sisters. Research instruments employed were: (1) Questionnaire on sources and level of stress constructed by the researcher herself to measure the level of stress of the Sisters, (2) Comrey Personality Scale (CPs) to measure the personality traits of the Sisters. (3) Survey Questionnaire (SQ) constructed by the researcher to get the Sisters' background and (4) Questionnaire on coping mechanisms (CM) constructed by the researcher to identify coping mechanisms used and their effectiveness. Frequency, percentages, mean weights, standard deviations and ranking were used to analyze and interpret the data on sources and the level of stress, coping mechanisms, personality ratings and effectiveness of coping. The Pearson Product Moment correlation coefficient was computed to determine whether there was a significant correlation between the over-all, by area and by level of stress of the Sisters and their personality traits. This study yielded the following findings: 1. The Sisters experienced high level of stress in the area of community support and structures, especially the following: a. Superiors making major decisions without consulting the members of the community. b. Conflict within the Congregation arising from varied interpretation and implementation of the mission trust. c. Misunderstanding arising from misinterpretation of authority. 2. The Sisters' Personality ratings on the Comrey's Personality Scale ranged from high average (X = 66.1) to very high (X - 76.31) where empathy go the highest mean score of 76.31 followed by trust (X = 76.1).